Mineral Composition of Fruits of Seabuckthorn (Hippophae L.) Growing in Lahaul Valley of Himachal Pradesh - Singh, Virendra; Sharma, K. B. (Indian Forester, 2016)
Mineral composition (Zn, Cu, Fe, Ca, Mg, Na and K) of seabuckthorn fruit pulp and seed components were studied in 8 populations of seabuckthorn (H. rhamnoides ssp. turkestanica and H. salicifolia) growing in Lahaul valley (2600-3200 m asl), a dry temperate Himalayan region of Himachal Pradesh. In fruit pulp of H. rhamnoides, Zn varied from 8.7 to 12.5 ppm; Cu, 3.1-4.7 ppm; Fe, 427-800 ppm; Ca, 2310-3375 ppm; Mg, 500-585 ppm; Na, 55-137 ppm and K, 8575-10025 ppm and in seed, Zn varied from 20.7 to 27.8 ppm; Cu, 4.1-8.4 ppm; Fe, 18.1-74.7 ppm; Ca, 480-1380 ppm; Mg, 1080-1725 ppm; Na, 60- 133 ppm and K, 6225-9350 ppm. The values of Zn, Cu, and Mg were higher in the seeds as compared to pulp, where as other minerals (Fe, Ca and K) were higher in pulp, with the exception of Na, which was almost similar in both parts. The values for H. salicifoliawere in general in the range of H. rhamnoides populations.